1998
DOI: 10.1093/clinchem/44.12.2433
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of cardiac troponin I: implication for reliable immunodetection

Abstract: We have analyzed by different immunological methods the proteolytic degradation of cardiac troponin I (cTnI) in human necrotic tissue and in serum. cTnI is susceptible to proteolysis, and its degradation leads to the appearance of a wide diversity of proteolytic peptides with different stabilities. N- and C-terminal regions were rapidly cleaved by proteases, whereas the fragment located between residues 30 and 110 demonstrated substantially higher stability, possibly because of its protection by TnC. We conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(63 citation statements)
references
References 16 publications
3
59
0
1
Order By: Relevance
“…The stable core region lies between amino acid residues 30 and 110. 32 The ADVIA Centaur immunoassay uses antibodies that recognize immunologic epitopes located within this stable region.…”
Section: Discussionmentioning
confidence: 99%
“…The stable core region lies between amino acid residues 30 and 110. 32 The ADVIA Centaur immunoassay uses antibodies that recognize immunologic epitopes located within this stable region.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these differences may be that clearance of recombinant cTnI subunits is not representative of in vivo clearance, as the majority of naturally occurring circulating cTnI is found in complex with other troponin subunits [30]. Additionally, free cTnI subunits are more vulnerable to degradation by serum proteases, which may have shortened apparent halflife in some studies [31]. The half-life in our study may have also been affected by several further factors.…”
Section: Discussionmentioning
confidence: 90%
“…During myocardial necrosis, proteolytic enzymes are released from lysosomes and act on contractile proteins within hours after the initial insult. A study by Katrukha et al found that fragmentation of cTnI occurred within 2 h of tissue necrosis and was most profound in free cTnI rather than in complex [71]. This fragmentation was most apparent in the regions at the extreme end of the C-and N-terminus, whereas amino acid residues in the more central regions were largely preserved, probably due to protection from proteases.…”
Section: Target Degradationmentioning
confidence: 99%
“…This could have profound effects on measurable troponin levels, because free troponin I may have a shorter half-life than that in complex. Test antibodies may also vary in their affinity for free cTnI [71]. Given that anticoagulants have been shown to affect assay results, the logical choice would be to use serum.…”
Section: Anticoagulantsmentioning
confidence: 99%